Penegakan Hukum Administrasi Negara dalam Penanganan Pencemaran Lingkungan - Pasaribu, Anjelina; Febriana, Febriana; Sanusi Hasibuan, Rizal; Ramadhan, Taufiq (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract The national environmental law development agenda includes the creation of environmental administration law ideas, especially those related to the supervision of environmental management from a policy and legal perspective. In the context of the basic framework for national development, law has two sides. The concept of environmental administration law in monitoring environmental management which is based on UUPPLH is based on several things that require change or development that is more progressive, not conservative. It cannot be denied that institutions are very important for overseeing environmental management. According to Law no. 32 of 2009, legal efforts that can be taken in cases of environmental pollution by industry fall into three categories: law enforcement efforts in the administrative, criminal and civil fields. Law Number 32 of 2009 concerning Environmental Protection and Management, in addition to the government's authority to determine administrative sanctions, there are also strengthening aspects, namely forms of administrative sanctions and Regulation of the Minister of Environment of the Republic of Indonesia Number 2 of 2013 concerning guidelines for implementing administrative sanctions. in the field of environmental protection and management. Keywords: Environment, State Administrative Law, Law Abstrak Agenda pembangunan hukum lingkungan hidup nasional mencakup penciptaan gagasan hukum administrasi lingkungan, terutama yang berkaitan dengan pengawasan pengelolaan lingkungan hidup dari sudut pandang kebijakan dan hukum. Dalam konteks kerangka dasar pembangunan nasional, hukum memiliki dua sisi. Konsep hukum administrasi lingkungan dalam pengawasan pengelolaan lingkungan hidup yang didasarkan pada UUPPLH didasarkan pada beberapa hal yang menuntut perubahan atau pengembangan yang lebih progresif, bukan konservatif. Tidak dapat dipungkiri bahwa kelembagaan sangat penting untuk mengawasi pengelolaan lingkungan hidup. Menurut UU No. 32 Tahun 2009, upaya hukum yang dapat dilakukan dalam kasus pencemaran lingkungan oleh industri termasuk dalam tiga kategori: upaya penegakan hukum dalam bidang administrasi, pidana, dan perdata. Undang-Undang Nomor 32 Tahun 2009 tentang Perlindungan dan Pengelolaan Lingkungan Hidup di samping adanya kewenangan pemerintah atas penetapan sanksi administratif di dalamnya juga terdapat aspek penguatan yaitu bentuk-bentuk sanksi administratif dan Peraturan menteri lingkungan hidup Republik Indonesia Nomor 2 tahun 2013 tentang pedoman penerapan sanksi administratif di bidang perlindungan dan pengelolaan lingkungan hidup. Kata Kunci : Lingkungan, Hukum Administrasi Negara, Undang- Undang